Duolinggo As An Attractive Application To Upgrade Student’s Motivation In Learning English Independently - Mezia Kemala Sari; Nurul Hadina; Nahla Rahmanda (LPPM Universitas Muhammadiyah Sumatera Barat, 2022)
As one of the modern, simple and easy to use application in learning English, Duolinggo is popular to help facilitation students or English learner in acquiring foreign language. This research purposes to investigate the students’s motivation in learning English indenpendently by using educational tools like Duolinggo everywhere. Quantitative research was used to explore the phenomenon. There are 16 students participated in this resaech from SMP Muhammadiyah Padangpanjang. The techniques of collectiong data are by using quitionaire and after they use Duolinggo outside the classroom and learn by themselves. The result of this research are 75% students agree percentage that Duolinggo really encourage them in learning English indenpendently, 62,5% students agree that Duolinggo can give opportunities to them to learn English better, while 43,75% students agree that Duolinggo encourage them to spend more time learning English outside of the classroom. It has the same percentage with another situation like Duolinggo make English learning more enjoyable and interesting and It is more fun to practice Duolinggo in the smartphone than in the classrrom. It can be conclude that students can be more motivated in learning English independently by using Duolinggo as one of the suppoting educational learning tool.Keywords: Duolinggo, Gamification, Student’s motivation, Learning Independently